Essence bank guarantee in procurement of government goods/services - Mochammad Hudjir; Slamet Suhartono; Endang Prasetyawati; Sri Setyadji (Technium Social Sciences Journal, 2021)
This research is a normative legal research that examines the positive law related to gank guarantees in the procurement of government goods/services. The philosophy of forming a state is to create public welfare, and to achieve this goal the government must carry out development. One of the important and vital development sectors is the construction of construction services to support the socio-economic activities of the community to support the realization of national development goals. The construction of construction services aims to provide a direction for the growth and development of the economic sector, particularly in realizing a strong, reliable, highly competitive and efficient business structure. The essence of a Bank Guarantee in the procurement of government good/services is a guarantee agreement that aims to provide guarantees to users of government goods/services, from the possibility of default of government goods/service providers